Chronic meningitis: a diagnostic challenge highlighted in a case of cryptococcal meningoencephalitis in an apparently immunocompetent older woman. (14th October 2011) - Patel, Chirag; Rabindra, Ramila; Hashemi, Nima; Ward, Michael; Mannan, Jayamalathy Mannar
Abstract : Chronic meningitis can be difficult to diagnose. The authors report the case of an older Caucasian lady, with no underlying immunocompromising factors, who presented with a 2 month history of confusion. Due to the non-specific symptoms on presentation, a diagnosis was only obtained after a repeat CT scan of the brain, which showed hydrocephalus. Subsequent cerebrospinal fluid analysis showed biochemical abnormalities and Cryptococcus neoformans on staining.